The Influence Of Capital Expenditure, Total Debt To Total Assets, Total Debt To Equity And Long Term Debt To Total Equity On Profitability In Manufacturing Companies Listed On The Indonesian Stock Exchange In 2014-2018 - Cecilia Riau Ekowati; Sylvia Sari R; Kasful Anwar (LPPM Universitas Respati Indonesia, 2024)
This study aims to analyze the Effect of Capital Expenditure, Total Debt to Total Assets, Total Debt to Equity and Long Term Debt to Total Equity on Profitability in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2018. This research is an explanatory research that explains the causality relationship using secondary data with the population are all Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2018. A sample of 11 companies was selected using the purposive sample method in accordance with predetermined criteria including being listed on the IDX and delivering in full accordance with the information needed, namely Capital Expenditure, Total Debt to Total Assets, Total Debt to Equity and Long Term Debt to Total Equity and profitability measured through ROA during the period 2014 - 2018. The analytical method used is linear regression panel data. The results showed that at 95% confidence level of the four dependent variables studied were: Capital Expenditure, Total Debt to Total Assets, Total Debt to Equity and Long Term Debt to Total Equity, there was one variable that had a significant effect on Profitability in Registered Manufacturing Companies on the Indonesia Stock Exchange in 2014-2018 namely and Long Term Debt to Total Equity. Meanwhile, if tested simultaneously Capital Expenditure, Total Debt to Total Assets, Total Debt to Equity and Long Term Debt to Total Equity have a significant effect on profitability. Keywords : Capital Expenditure, Total Debt to Total Assets, Total Debt to Equity, Long Term Debt to Total Equity and Profitability